A Wavelet Evaluation of Some Leading Business Cycle Indicators for the German Economy - Jens J. Krüger (Journal of Business Cycle Research, 2021)
Leading indicators are important variables in business cycle forecasting. We use wavelet analysis to investigate the lead-lag stability of German leading indicators in time-frequency space. This method permits a time-varying relation of the leading indicators to the reference cycle allowing simultaneously to focus on lead-lag stability at the specific business cycle frequencies. In this way we analyze an index of new orders, a survey-based index of business expectations, an index of stock market returns and the interest rate term spread. We confirm that most of these indicators are indeed leading~the reference cycle most of the time, but the number of months leading varies considerably over time and is associated with a great deal of estimation uncertainty.
Keywords: C49; E32; E37; 330; Business cycle forecasting; Leading indicators; Wavelet analysis; Phase difference